A framework explaining the entrepreneurial intentions of engineering students in public universities - Arroyo, Pilar Ester; Cárcamo-Solís, María de Lourdes; Cuevas-Vargas, Héctor; Estrada-Rodríguez, Salvador (Cuadernos de Administración, 2021)
This study explains the Entrepreneurial Intent (EI) of university students enrolled in engineering programs at the public university of the state of Guanajuato, Mexico, in terms of the three constructs of the Theory of Planned Behavior, formal (entrepreneurship education) and informal (the entrepreneurial demonstrated behavior of family and friends) institutional factors, and two individual traits (innovativeness and need of achievement). The conceptual model proposed also examines the role of entrepreneurship education in strengthening entrepreneurial self-efficacy. Survey data is analyzed using structural equation modeling. Findings indicate entrepreneurial attitudes have the most significant predictive ability on entrepreneurial intention over entrepreneurial education and the manifest entrepreneurial actions of close social groups that have only a moderate influence on EI. The analysis also confirms that entrepreneurship education enhances entrepreneurial self-efficacy. Based on these results, it is recommended that Engineering Schools devote more attention to experiential learning to create favorable entrepreneurial attitudes and develop students’ entrepreneurial skills, particularly among those with a high need for achievement.